2018
DOI: 10.3233/ip-170045
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to innovating with open government data: Exploring experiences across service phases and user types

Abstract: Abstract. Open government data (OGD) can enable outbound open innovation (OI) that is beneficial to society. However, innovation barriers hinder OGD users from generating value. While previous studies have detailed a large number of such barriers, little is known of how different types of OGD users are affected, and when the barriers appear in their innovation processes. To this end, this paper describes a case study of distributed service development in the Swedish public transport sector. The contribution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 38 publications
3
74
1
1
Order By: Relevance
“…Based on the conducted research, it has been confirmed that barriers to the implementation of innovation projects vary in dependence on the company's profile [7]. The barriers to the implementation of innovative projects can be attributed to different causes and sources: innovation risks [6], financial aspects of implementing innovation projects, employee and management attitudes [33,34] constraints imposed by the environment in which the company operates [35], availability of information [10] and others. Finding out of effective ways to manage barriers to the implementation of innovative projects is a prerequisite for successful business operations [9].…”
Section: B Internal and External Support For Innovation Projectsmentioning
confidence: 89%
See 1 more Smart Citation
“…Based on the conducted research, it has been confirmed that barriers to the implementation of innovation projects vary in dependence on the company's profile [7]. The barriers to the implementation of innovative projects can be attributed to different causes and sources: innovation risks [6], financial aspects of implementing innovation projects, employee and management attitudes [33,34] constraints imposed by the environment in which the company operates [35], availability of information [10] and others. Finding out of effective ways to manage barriers to the implementation of innovative projects is a prerequisite for successful business operations [9].…”
Section: B Internal and External Support For Innovation Projectsmentioning
confidence: 89%
“…Through removal of barriers for implementation of innovation projects, the realization of new/improved products on the market and advancement of organizational processes and management structures convenient conditions are created under which the value of existing resources is increased and competitiveness of the company is empowered. The influence of diverse barriers on implementation of innovation projects has been widely studied [5,6,7,8,9,10] under different socio-economic contexts. Differences in obtained results point out clearly that structure of barriers for innovation projects depend highly on socio-economic and cultural environment in which the company operates.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, open data may provide flexible alternatives in comparison to traditional closed systems (e.g., mapping applications and interfaces). Open data has also impacted an extensive array of applications ranging from open government services [1][2][3] to numerous specific fields of science, ranging from e.g., pharmacy [4] to oceanography [5]. A widely studied open-data potential concerns broader concepts of open innovation, business logic, and platforms economics [6][7][8][9][10].…”
Section: Open Data and Innovation In Ports And The Maritime Sectormentioning
confidence: 99%
“…(1) • "Piers and their equipment has to be in good condition" (3) Safety and security: • "Passage control and security monitoring are nominal" (1, 3) • "Rites of passage are not always correctly limited" (1) • "Too easy access" (1) • "Moving in port areas is blurred as the guidance is missing" (3) • "Port manual exists but not in digitalized form" (2) • "Information distribution in deviant/hazardous situations concerning the whole port area" (3, 2, 1) • "When something happens (concerning security or environment) quick response is needed" (3) • "Real-time data concerning hazardous materials is missing" • "Chemicals pose a great risk" (3) • "Is there location data concerning hazardous materials?" (3, 2) Environment: • "Environmental stress caused by vessels and cargo" (3) • "Sloppy handling of fertilizers in uploading: fertilizers may end up in sea" (3) • "Authorities lack knowledge of environmental issues in ports" (3) •"Legal permits for environmental licenses (9 months) take too long for customers" (3) • "Waste handling points are too few and their condition data is limited"(3,2)…”
mentioning
confidence: 99%
“…Existem diretrizes para que indicadores e metadados correlatos à saúde sejam disponibilizados (OPAS-OMS 2008; Pereira e Tomasi 2016; WHO 2015) e algumas iniciativas contemplam a boa prática de disseminar dados abertos (Smith e Sandberg 2018;O'Neill et al 2017) . Porém, ainda que parte dos esforços recentes das determinações em saúde venham, invariavelmente, das ciências da computação, é incipiente o ensejo de apresentar conjuntamente, de forma documentada e reprodutível, códigos-fonte e material explicativo da transposição, análise e visualização de dados (Ross, Lehman, e Gross 2012) como parte do conhecimento que compõe a tomada de decisão via salas de situação.…”
unclassified